Determinants of household food security in the eastern region of Nepal (SAARC Journal of Agriculture, 2017)
Using the agricultural census data of 2011/12, this paper has attempted to identify the determinants of household level food security in the eastern region of Nepal. Being the censored type sample population, tobit model has been used. On an average, the households experienced no food shortages for 8.5 months, the cultivated land per household was 0.85 hectare and around 34 percent of the cultivated land was irrigated. The results showed that the size of the land holding, nearness to the market, male headed household, households members with agriculture and allied occupation and the educational level of household head were positive and significant variables while household size was negative and significant variable to food security. It was also revealed that the hills and the mountains were more food insecure than Terai region. Hence, investment in human capital, creation of off-farm employment opportunities, increasing physical access through markets and roads development and access to land and augmenting their quality are needed to further improve the food security situation. Similarly, special programs should be implemented targeting female headed households as they are more food insecure than male headed households.SAARC J. Agri., 14(2): 174-188 (2016)